Microwave heating mechanism and self-healing performance of asphalt mixture with basalt and limestone aggregates. (1st August 2022) - Wang, Fu; Zhu, Hongbin; Shu, Benan; Li, Yuanyuan; Gu, Dengjun; Gao, Yangming; Chen, Anqi; Feng, Jianlin; Wu, Shaopeng; Liu, Quantao; Li, Chao
Highlights: Basalt was a magnetic loss material with dielectric and magnetic loss properties. Basalt significantly increased the microwave heating rate of asphalt mixture. Evaluate self-healing performance with flexural strength and fatigue resistance. Basalt can improve microwave heating self-healing performance of asphalt mixture. Abstract: Traditional asphalt mixtures can't absorb microwave energy efficiently, which limits the development of microwave heating technology in the field of road maintenance. Based on the microwave heating characteristics of basalt aggregates, the overall microwave self-healing rate of the asphalt mixture can be enhanced. The basalt was tested by XRF, XPS, XRD and electromagnetic parameters to reveal its microwave heating mechanism. Through the heating rate test, SCB test and fatigue test of asphalt mixture, its heating characteristics, flexural strength, fatigue resistance and self-healing performance were studied. The results showed that the excellent wave-absorbing properties of basalt are highly correlated with the elements of Si, Fe and Al. Its TanδM was slightly larger than TanδE, which indicated that basalt can absorb microwave energy through dielectric loss and magnetic loss. The aggregate type and particle size both affected the microwave heating rate of the aggregates. After microwave heating, the flexural strength and fatigue resistance of asphalt mixture with basalt and limestone aggregates can recover at least 65% and 23% respectively.